Pengaruh Bentuk Bukaan Pada Lantai Bangunan Terhadap Tingkat Kenyamanan Termal Pada Rumah Panjang Suku Dayak Brusu Kecamatan Sekatak Provinsi Kalimantan Utara - Eko Wahyudi; Sholehah Sholehah (Borneo Engineering : Jurnal Teknik Sipil, 2019)
The longhouse is a home for Brusu Dayak tribes who live in North Kalimantan, which always develops as the building length increases following the increase in the number of family heads in one family. Compared to other Dayak houses, long brusu Dayak tribes have no windows but rely solely on openings on the roof and openings on the building floor as ventilation ventilation. This affects the thermal comfort of the longhouse. In general, this study aims to determine how much influence the shape of the openings on the floor of the brusu dayak longhouse building on the level of thermal comfort.The method in this study includes direct observation of the spaciousness of the shape of the building and the shape of the floor openings in the longhouse, as well as direct measurement at several points that have been determined, namely: measurement of temperature, humidity, air movement using several measuring devices, namely: thermometer, anemometer, hygro thermometer and iinfrared thermometer, measurements are made on the interior of a long house with 15 measuring points, where each point is measured for 24 hours with a measurement time every 2 hours. The results of this study note that the shape of the openings on the floor affects the level of thermal comfort in the longhouse, this is evidenced when the condition of the floor hole is closed there is an increase in the effective temperature in the room even though the increase in the effective temperature is not significant.